2018
DOI: 10.1002/rem.21550
|View full text |Cite
|
Sign up to set email alerts
|

Fungal biotransformation of 6:2 fluorotelomer alcohol

Abstract: Fungal degradation of 6:2 fluorotelomer alcohol (6:2 FTOH, C 6 F 13 CH 2 CH 2 OH) by two wooddecaying fungal strains and six fungal isolates from a site contaminated with per-and polyfluoroalkyl substances (PFASs) was investigated. 6:2 FTOH is increasingly being used in FTOH-based products, and previous reports on the microbial fate of 6:2 FTOH have focused on bacteria and environmental microbial consortia. Prior to this study, one report demonstrated that the 6:2 FTOH biotransformation by the wood-decaying fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The 3-fluoro 5:3 acid formed from the preferred hydrogenation pathway in the anaerobic defluorinating enrichment was not detected during the aerobic biotransformation (Figure S23B–D). 6:2 FTUCA is a key biotransformation intermediate of 6:2 fluorotelomer alcohol (6:2 FTOH, a component of coating material in commercial products) under aerobic conditions by various microbial communities and microbial species. ,, Many of the previously reported TPs were also detected here (Figure S23B–D), and among them, C6a (PFHxA) and C5a (PFPeA) were two major ones. We also detected two new TPs (2H-PFHpA and 2H-PFHxA) (Figures S23D and S24), which were not reported in previous studies on 6:2 FTOH .…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The 3-fluoro 5:3 acid formed from the preferred hydrogenation pathway in the anaerobic defluorinating enrichment was not detected during the aerobic biotransformation (Figure S23B–D). 6:2 FTUCA is a key biotransformation intermediate of 6:2 fluorotelomer alcohol (6:2 FTOH, a component of coating material in commercial products) under aerobic conditions by various microbial communities and microbial species. ,, Many of the previously reported TPs were also detected here (Figure S23B–D), and among them, C6a (PFHxA) and C5a (PFPeA) were two major ones. We also detected two new TPs (2H-PFHpA and 2H-PFHxA) (Figures S23D and S24), which were not reported in previous studies on 6:2 FTOH .…”
Section: Resultsmentioning
confidence: 63%
“…The biodefluorination of fluorinated compounds (mostly the polyfluorinated structures) has been previously reported. The defluorination was typically initiated by HF elimination at the α and β positions for polyfluorocarboxylic acids ,,, or by desulfonation for polyfluorosulfonic acids. ,,, Compared to biotransformation of polyfluorinated compounds, convincing reports on microbial cleavage of C–F in perfluorinated structures are even fewer. ,, Based on fluoride formation and transformation product identification, our recent study has reported microbial reductive defluorination of two branched unsaturated per- and polyfluorinated carboxylic acids in an anaerobic enrichment . It suggested that the biotransformation and biodefluorination of fluorinated carboxylic acids (FCAs) might be structure-dependent and that the CC double bond could play an essential role in the reductive defluorination of FCA.…”
Section: Introductionmentioning
confidence: 98%
“…Thus far, tremendous efforts have been invested in understanding the environmental fate and transport of FCAs using microcosms and microbial isolates. ,,, , In Table , we summarized the aerobic defluorination reported in the literature and this study for C 2 –C 10 FCAs and the alcohol precursors oxidizable to carboxylic acids. In the table, all defluorinated structures share a common feature: a functional group subject to enzymatic defluorination or nondefluorinating reactions that form unstable intermediates with fluoroalcohol moieties causing spontaneous C–F cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the carbon source in the droplet media on growth is limited, given that when droplets were incubated (27 °C, 2 days) in minimal media without any carbon source, we found several C. rosea spores germinating and developing hyphae. This can be explained by spore germination being mainly dependent on the presence of water and oxygen 45 , or C. rosea could have a mechanism to access the carbon chain of fluorinated surfactants in the HFE oil since the ability to degrade fluorinated compounds has been demonstrated for other fungi [46][47][48] .…”
Section: Improving Droplet Incubation For Filamentous Fungi To Analyz...mentioning
confidence: 99%